Transcatheter “valve-in-valve” implantation of bioprosthesis in failed surgical tricuspid bioprosthesis (first experience in Russia) - T. E. Imaev; A. E. Komlev; V. V. Romakina; P. M. Lepilin; M. I. Makeev; A. S. Kolegaev; A. A. Margolina; O. V. Sapelnikov; I. S. Fedotenkov; M. A. Saidova; R. S. Akchurin (Российский кардиологический журнал, 2019)
Aim. In the issue we report first in Russia experience of transcatheter “valve-invalve” implantation (TVIV) for treatment of severe tricuspid stenosis due to the structural deterioration of surgical tricuspid bioprosthesis.Material and methods. TVIV was performed in 4 high-risk redo patients (1 to 3 previous sternotomies) of various ages across (18-68 years) with structural deterioration of surgical tricuspid bioprosthesis.Results. Technical success was achieved in 100% cases. Diastolic gradients on tricuspid valve markedly decreased in all patients. Peak transtricuspidal gradient decreased from 20,4 to 10 mmHg in average. Clinical improvement as assessed by 6-minute walk test after TVIV was observed in 3 patients with congestive heart failure. In 1 patient with asymptomatic right ventricle dysfunction TVIV resulted in the enhancement of echocardiographic parameters.Conclusion. TVIV is a mininvasive alternative to conventional surgical tricuspid valve redo replacement. Based on available data including own experience TVIV should be considered an effective and safe treatment option for failed TV bioprostheses in high-risk patients of different age. Further studies are needed to assess long-term results of the method.